Methodology to evaluate the operational suitability of electromobility systems for urban logistics operations - Teoh, Tharsis (2018)
A methodology was developed to evaluate the operational suitability of electromobility concepts for last-mile delivery operations. Electromobility systems consisting of electric vehicles of ten weight classes and four mid-operation charging strategies were synthesized and evaluated using a hypothetical grocery outlet replenishment scenario. A system of operational suitability indicators was developed based on the amount of and efficiency of resources needed. The results highlight a strong trade-off between single-charge driving range, payload capacity, and the minimum fleet size needed. If operational performance similar to that of diesel vehicles is to be reached, mid-operation charging could be a reasonable alternative to “simply” having a bigger vehicle battery.